Cultivo in vitro, citogenética e aplicação de fungos micorrízicos arbusculares (Glomeromycota) no estabelecimento ex vitro de variedades e do híbrido apirênico intraespecífico de videira (vitis vinifera L.) - Menezes, Eiryanne Fonseca de (2013)
The grapevine is one of the most important crops in the San Francisco Valley, to be an important generator of income and social development. It is noteworthy production for the domestic and foreign market, whose requirements demand the need for competitive development of new genetic material to the producer. In this case, the breeding program for cultivation in tropical conditions has employed the crossing of varieties of seedless grapes, using as support embryo rescue technique, which enables the acquisition of hybrid course. Moreover, the cytogenetic characterization of hybrids and parental emerges as a tool that can generate important data for the breeding programs of the grapevine. Counterpart, micropropagation, which is the wider applicability of the technique of tissue culture, has, as one of the many advantages, the large scale production of plants in less time than usual and pathogen-free. During the acclimatization phase of grapevine micropropagation significant losses occur. The various benefits they provide, mycorrhizal fungi are an alternative because they reduce losses, making the transition less stressful conditions in vitro to ex vitro. This study aimed to evaluate cytogenetically vine varieties and hybrids, as well as study the mycorrhizal association in ex vitro establishment of plantlets, trying to select isolates effective in promoting growth and nutrient uptake in apirenic hybrid grapesvines.